2013
DOI: 10.1210/jc.2012-3045
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Adrenal Lesions Using [123I]IMTO-SPECT/CT

Abstract: [(123)I]IMTO is a highly specific radiotracer for imaging of adrenocortical tissue with a short investigation time and low radiation exposure. Because of the general availability of SPECT technology, [(123)I]IMTO scintigraphy has the potential to become a widely used tool to noninvasively characterize the biology of adrenal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…43,44 However, 98% of the NFAs in our series also exhibited CYP11B1 staining, and both 11C-metomidate uptake and 123 I-iodometomidate uptake in NFA have been demonstrated in clinical studies. 45,46 CYP11B1 downregulation may be achieved in normal surrounding adrenocortical tissue by dexamethasone pretreatment. However, it is unclear whether this also holds true for adrenocortical adenoma cells because ACTH (adrenocorticotropic hormone) receptor expression is low in NFAs.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 However, 98% of the NFAs in our series also exhibited CYP11B1 staining, and both 11C-metomidate uptake and 123 I-iodometomidate uptake in NFA have been demonstrated in clinical studies. 45,46 CYP11B1 downregulation may be achieved in normal surrounding adrenocortical tissue by dexamethasone pretreatment. However, it is unclear whether this also holds true for adrenocortical adenoma cells because ACTH (adrenocorticotropic hormone) receptor expression is low in NFAs.…”
Section: Discussionmentioning
confidence: 99%
“…IMTO does show uptake in metastasis of ACC (Hahner et al 2013. In two studies, sensitivity and specificity for characterization of adrenal lesions was 89% and 85%, and 38% and 100% respectively (Hahner et al 2013.…”
Section: Future Directions In Diagnosing Accmentioning
confidence: 95%
“…IMTO does show uptake in metastasis of ACC (Hahner et al 2013. In two studies, sensitivity and specificity for characterization of adrenal lesions was 89% and 85%, and 38% and 100% respectively (Hahner et al 2013. Early results suggest that proton MR spectroscopy may be useful in discriminating pheochromocytomas and adrenal adenomas from adrenal metastases and ACC.…”
Section: Future Directions In Diagnosing Accmentioning
confidence: 99%
“…[123I]IMTO for single photon emission computed tomography (SPECT) and planar scintigraphy has proved a valuable alternative to PET imaging with a sensitivity of 89 % and a specificity of 85 % for differentiating adrenocortical tumors from lesions of non-adrenocortical origin [47]. A recent report in a larger series of patients with adrenocortical cancer has shown that only a subset of ACCs is clearly positive by SPECT/CT iodometomidate imaging [48].…”
Section: Pet-pet/ctmentioning
confidence: 99%